PENGELOLAAN PEMBIAYAAN PENDIDIKAN DI SMP - Anis Pratiwi (UNIVERSITAS BENGKULU, 2016)
The purpose of this research is to evaluate the planning, implementation, transparency and accountability the educational funding management at Public Yunior High school 02 Ketahun Nort Bengkulu. The subject of this research were the principal, school committee, school treasurer, and teacher. The method of this research was a evaluative descriptive method with context, input, process, product (CIPP) approach. The data collecting technique used interview, observation, and documentation. The result of this research showed that the achievement of the short and long term of education funding planning, implementation, transparency and accountability was the approaching fit category by the provision of funding management in the school.Keywords: management, funding of education